212k views
5 votes
2. 2x+6y=6
-x-3y = -3
Solution(s):
PLEASE HELP SOLVE FOR X AND Y

User Dayde
by
5.6k points

1 Answer

1 vote

Answer:

x = 0, y = 1

Explanation:

2x + 6y = 6 → (1)

x - 3y = - 3 ( add 3y to both sides )

x = 3y - 3 → (2)

substitute x = 3y - 3 into (1)

2(3y - 3) + 6y = 6 ← distribute parenthesis and simplify left side

6y - 6 + 6y = 6

12y - 6 = 6 ( add 6 to both sides )

12y = 12 ( divide both sides by 12 )

y = 1

substitute y = 1 into (2)

x = 3(1) - 3 = 3 - 3 = 0

solution is x = 0 , y = 1

User Antony Denyer
by
5.0k points